Dampak Alih Fungsi Trotoar Terhadap Kinerja Operasionalnya di Jl.Ahmad Yani, Kabupaten Sidoarjo. - Fadhilatuz Zahroh; Ika Naya Guruwati; Mega Ayundya Widiastuti; Novi Puspitasari (JURNAL SIMETRIK, 2026)
The conversion of sidewalks into parking areas and informal activity spaces remains a persistent issue that reduces the quality of pedestrian facilities and disrupts their primary function as safe, comfortable, and barrier-free public spaces. This study examines the impact of such conversions on sidewalk operational performance through field observations using a quantitative approach, including measurements of pedestrian flow, walking speed, density levels, and movement space across three different time periods. The results indicate a significant decline in service levels, characterized by increased movement barriers, reduced effective lane width, and decreased accessibility. The variables of travel time and density also show reduced performance in segments with higher economic activity. These findings highlight the need for spatial reorganization through infrastructure improvements, regulation of informal activities, and consistent enforcement of policies. Inclusive design approaches and strategies such as street diets, as recommended in international studies, can serve as references for improving sidewalk quality to ensure they remain safer, more functional, and more equitable. Keywords: Conversion Of Sidewalks, Operational Performance Of Sidewalks, Pedestrian Paths